Stališča osnovnošolskih učiteljev do zagotavljanja discipline pri športni vzgoji - Tamše, Majda; Planinšec, Jurij (Revija za elementarno izobraževanje, 2010)
Opinion of primary school teachers toward insuring discipline in sports education. The goal of our research, which included 57 primary teachers, was to discover the teachers’ views of managing discipline during physical education in the first six years of primary school. Through an analysis using the Mann-Whitney’s test we wanted to study the different strategies that teachers use to manage discipline during physical education and to find out if there are any differences on the basis of the amount of experience a teacher has (experienced or novice) and the location of the teaching (rural or urban). The results obtained show that teachers with less experience use a more pupil-oriented approach to managing discipline in the classroom, while the experienced teachers use a reactive approach to managing discipline. Experienced teachers perceive themselves as the key actors on whom the discipline of a group depends. The results can fill us with optimism that we are on the way to enforcing a more democratic type of management in our classrooms.